Assessing cough symptom severity in refractory or unexplained chronic cough: findings from patient focus groups and an international expert panel. Issue 1 (14th March 2022) - Kum, Elena; Guyatt, Gordon H.; Munoz, Caroline; Beaudin, Suzanne; Li, Shelly-Anne; Abdulqawi, Rayid; Badri, Huda; Boulet, Louis-Philippe; Chen, Ruchong; Dicpinigaitis, Peter; Dupont, Lieven; Field, Stephen K.; et al.
Background: Cough symptom severity represents an important subjective end-point to assess the impact of therapies for patients with refractory or unexplained chronic cough (RCC/UCC). As existing instruments assessing the severity of cough are neither widely available nor tested for measurement properties, we aim to develop a new patient-reported outcome measure addressing cough severity. Objective: The aim of this study was to establish items and domains that would inform development of a new cough severity instrument. Methods: Three focus groups involving 16 adult patients with RCC/UCC provided data that we analysed using directed content analysis. Discussions led to consensus among an international panel of 15 experts on candidate items and domains to assess cough severity. Results: The patient focus group provided 48 unique items arranged under broad domains of urge-to-cough sensations and cough symptom. Feedback from expert panel members confirmed the appropriateness of items and domains, and provided an additional subdomain related to cough triggers. The final conceptual framework comprised 51 items in the following domains: urge-to-cough sensations (subdomains: frequency and intensity) and cough symptom (subdomains: triggers, control, frequency, fit/bout duration, intensity, quality and associated features/sequelae). Conclusions: Consensus findings from patients and international experts established domains of urge-to-cough and cough symptom with associated subdomains and relevant items. The results support item generation and content validity for a novel patient-reported outcome measure for use in health research and clinical practice. The urge-to-cough (subdomains: frequency and intensity) and cough symptom (subdomains: triggers, control, frequency, fit/bout duration, intensity, quality, and associated features/sequelae) represent domains to assess cough severity in RCC/UCC https://bit.ly/3fI6qkC